[Rigo] - Esmerelda Landin::::::photographer::: (2005)
Description supplied by photographer: 'Aquí está mi primo, Rigo. Trabaja cortando la hierba que crece alrededor de los árboles de aguacate en el cerro en San Juan Nuevo.' Translation of description: 'This is my cousin, Rigo. He is workin in el cerro [the mountains] in San Juan Nuevo cutting the grass around the avocado trees.'